Pengaruh Current Ratio, Debt To Equity Ratio, Return on Assets, dan Total Asset Turnover terhadap Harga Saham: (Study Empiris pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman Terdaftar di Bursa Efek Indonesia (BEI) Periode 2019 – 2023) - Assyfa Putri Utami; Muhammad Jusman Syah (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research aims to determine the influence of the Current Ratio, Debt to Equity Ratio, Return on Assets, and Total Asset Turnover on Stock Prices. This research method uses a quantitative research design. The population in this study was 44 companies and the sample used was 20 companies selected using a purposive sampling technique in the Food and Beverage sub-sector listed on the Indonesia Stock Exchange for the 2019 - 2023 period. This research used multiple linear statistical analysis tools assisted by the SPSS program version 27. The research results show that partially and simultaneously the Current Ratio, Debt to Equity Ratio, Return On Assets and Total Asset Turnover have a positive and simultaneous effect on Stock Prices.